Staphylococcus aureus Exfoliative Toxin E, Oligomeric State and Flip of P186: Implications for Its Action Mechanism - Gismene, Carolina [UNESP]; Gonzalez, Jorge Enrique Hernandez [UNESP]; Santisteban, Angela Rocio Nino [UNESP]; Nascimento, Andrey Fabricio Ziem; Cunha, Lucas dos Santos; Moraes, Fabio Rogerio de [UNESP]; Oliveira, Cristiano Luis Pinto de; Oliveira, Caio C.; Provazzi, Paola Jocelan Scarin[UNESP]; Pascutti, Pedro Geraldo; Arni, Raghuvir Krishnaswamy [UNESP]; Mariutti, Ricardo Barros [UNESP] (Mdpi, 2022)
Staphylococcal exfoliative toxins (ETs) are glutamyl endopeptidases that specifically cleave the Glu381-Gly382 bond in the ectodomains of desmoglein 1 (Dsg1) via complex action mechanisms. To date, four ETs have been identified in different Staphylococcus aureus strains and ETE is the most recently characterized. The unusual properties of ETs have been attributed to a unique structural feature, i.e., the 180 degrees flip of the carbonyl oxygen (O) of the nonconserved residue 192/186 (ETA/ETE numbering), not conducive to the oxyanion hole formation. We report the crystal structure of ETE determined at 1.61 angstrom resolution, in which P186(O) adopts two conformations displaying a 180 degrees rotation. This finding, together with free energy calculations, supports the existence of a dynamic transition between the conformations under the tested conditions. Moreover, enzymatic assays showed no significant differences in the esterolytic efficiency of ETE and ETE/P186G, a mutant predicted to possess a functional oxyanion hole, thus downplaying the influence of the flip on the activity. Finally, we observed the formation of ETE homodimers in solution and the predicted homodimeric structure revealed the participation of a characteristic nonconserved loop in the interface and the partial occlusion of the protein active site, suggesting that monomerization is required for enzymatic activity.
Keywords: Staphylococcal exfoliative toxin E; Proline flip; Homodimerization; X-ray diffraction; Molecular dynamics